Analysis of Elementary Students' Participation Levels in Hockey Extracurricular Activities - Rahma Dwi Aulia; Yogi Akin; Wulandari Putri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the level of participation of elementary school students in hockey extracurricular activities in Bandung City. The study used a quantitative approach with a descriptive method to describe the level of student participation objectively based on numerical data. The research sample consisted of 50 students who participated in hockey extracurricular activities. The instrument used was a closed questionnaire with 18 statements using the Guttman scale, where the answer "Yes" was given a score of 1 and "No" was given a score of 0. The data obtained were analyzed using descriptive statistics with the help of SPSS software through the calculation of total scores, averages, percentages, and frequency distributions. The results showed that the classification of categories, the level of student participation was in the moderate category. The frequency distribution showed that most students were in the moderate and low categories, thus indicating that student participation in hockey extracurricular activities was not optimal. Therefore, efforts are needed to improve through more structured coaching, increased student motivation, and support from the school and parents so that student participation can increase more optimally